EFEKTIFITAS PEMBELAJARAN PAI BERBASIS BOARDING SCHOOL DI SMP KHAIRUNNAS TUBAN - M Wildan Dzil Azmi; M. Syarif Maulana Aditya (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study investigates the effectiveness of Islamic Religious Education (PAI) learning within a boarding school–based system at SMP Khairunnas Tuban by examining how instructional practices, religious habituation, and asrama culture interact to shape students’ character and religious behavior. Using a descriptive qualitative design, data were collected through in-depth interviews with diniyah teachers, participatory observation, and documentation of daily activities in both the classroom and the dormitory environment. Findings reveal that the integrated learning model combining formal PAI instruction, structured diniyah programs, continuous religious routines, and intensive teacher supervision creates an immersive educational atmosphere that significantly strengthens students’ discipline, moral awareness, and daily worship practices. Diniyah activities, particularly kitab learning and Qur’an memorization, function as the main medium of value internalization, while teachers’ role modelling reinforces moral consistency through real life examples. A disciplined dormitory structure further shapes responsible behavior and strengthens students’ self-regulation. Nevertheless, challenges such as dense schedules, student fatigue, and the need to balance firmness with compassion highlight the importance of pedagogical adjustments to maintain students’ motivation and well-being. The study contributes new insights by providing empirical evidence on the implementation of boarding-based PAI within a general junior high school context, a setting less explored in previous research. These findings offer practical implications for schools seeking to integrate academic, religious, and character education in a holistic and sustainable manner.